Poly (ADP-ribose) polymerase inhibitors combined with other small-molecular compounds for the treatment of ovarian cancer. Issue 6 (July 2019) - Liu, Lanlan; Liu, Peng; Liang, Zhiquan; Li, Ruyan; Shen, Mingxiang; Xu, Han; Ren, Dewan; Ji, Mengchen; Yang, Yuhua; Lu, Ziwen; Shang, Dongsheng; Zhang, Yibang; et al.
Abstract : Ovarian cancer is a heterogeneous disease with complex molecular and genetic hallmarks. Benefitting from profound understanding of molecular mechanisms in ovarian cancer pathogenesis, novel targeted drugs have been actively explored in preclinical studies and clinical trials. Considered as one of the most potent and effective targeted therapies for the treatment of ovarian cancer, poly (ADP-ribose) polymerase (PARP) inhibitors (PARPis) take advantages of synthetic lethality mechanisms to prevent DNA damage repair in cancer cells and cause their death, especially in cancers with BRCA mutations. Mounting evidence has indicated that the combination of PARPis with cytotoxic drugs or other targeted drugs has shown favorable synergistic effects. Excitingly, the antitumor activity of combination therapy of PARPis has been actively tested in multiple clinical trials and in-vitro or in-vivo experiments. In this review, we will briefly discuss the molecular mechanisms of PARPis combined with other therapeutic small-molecular compounds for the treatment of ovarian cancer.